2007
DOI: 10.1590/s1516-89132007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a beta-Glucanase produced by Trichoderma harzianum showing biocontrol potential

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 24 publications
(33 reference statements)
3
23
0
Order By: Relevance
“…Similar values have been reported, but the optimum temperature of M. perniciosa was lower when compared to most others (Nagata et al 1990, Fontaine et al 1997, Bara et al 2003, Marco and Felix 2007, and higher in relation to T. harzianum (Théodore and Panda 1995). Murray et al (2001) have also pointed out that the thermal stability of the T. emersonii enzyme is noteworthy because the estimated t 1/2 values at 70 • C and 80 • C were 136 min and 25 min, respectively, while 15% of the original activity remained after 15 min at 100 • C in the absence of substrate.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar values have been reported, but the optimum temperature of M. perniciosa was lower when compared to most others (Nagata et al 1990, Fontaine et al 1997, Bara et al 2003, Marco and Felix 2007, and higher in relation to T. harzianum (Théodore and Panda 1995). Murray et al (2001) have also pointed out that the thermal stability of the T. emersonii enzyme is noteworthy because the estimated t 1/2 values at 70 • C and 80 • C were 136 min and 25 min, respectively, while 15% of the original activity remained after 15 min at 100 • C in the absence of substrate.…”
Section: Discussionsupporting
confidence: 83%
“…Notario et al (1976) found that the β-1,3-glucanases are acidic proteins, and our results agree with theirs. Similar values of pH have been reported for β-1,3-glucanases from other fungi, including Trichoderma harzianum (Marco and Felix 2007) and Trichoderma asperellum (Bara et al 2003).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Chitinase [E. C. 3.2.1.14] and b-1,3-glucanase [E. C. 3.2.1.39] production were estimated quantitatively using the method described by De Marco and others (2000) and De Marco and Felix (2007), respectively. The cultures were grown in Trichoderma liquid medium for obtaining the supernatant.…”
Section: Physiological and Biochemical Characterization Of Selected Amentioning
confidence: 99%
“…In this work, the molecular weight (MW) of related esterases was estimated applying the principles described above. Such procedure has the advantage of allowing a preliminary MW determination without any previous protein purification method, such as Bio-Gel (Sierecka, 1998), Phenyl Sepharose (Marco and Felix, 2007) or Chitosan gel column (Tang and Qian, 2007). Two esterases, EST-4 and EST-5, found in the sibling species pair Drosophila mojavensis and D. arizonae, well characterized by Zouros and Johnson (1976), were selected.…”
Section: Introductionmentioning
confidence: 99%